Protective effect of growth differentiation factor 15 in sepsis by regulating macrophage polarization and its mechanism. Issue 4 (1st April 2022) - Zhang, Xinliang; Dong, Shimin
ABSTRACT: This study aims to investigate the protective effect of growth differentiation factor 15 (GDF15) in sepsis by regulating macrophage polarization and its mechanism. The mouse macrophages were cultured and treated with lipopolysaccharide (LPS), and some cells were intervened with GDF15 and LY294002. The proinflammatory activated (M1) macrophages and the anti-inflammatory activated (M2) macrophages were measured and observed, and the messenger RNA expression levels of their biomarkers, phosphatidylinositol 3-kinase (PI3K), and protein kinase B (Akt) were detected. The survival rate, cardiac function, and histopathological sections were observed. In the LPS group, after GDF15 intervention, the percentage of M1 macrophages decreased and M2 macrophages increased, the infiltration of monocytes/macrophages into the heart was inhibited, systemic and cardiac inflammation was reduced, and the survival time of the mice was prolonged. GDF15 regulated macrophage polarization and played an anti-inflammatory role by activating the phosphorylation of the PI3K/Akt signaling pathway. In patients with sepsis, the serum GDF15 level increased and was closely related to the severity of the sepsis and the 28-day mortality rate and could be used as a prognostic marker of sepsis. GDF15 regulates macrophage polarization through activating the PI3K/Akt signaling pathway and has a protective effect on survival and the cardiac function of patients with sepsis and sepsis mouse models. The increase in serum GDF15 level is closely related to severity and mortality in patients with sepsis and is therefore a prognostic marker of sepsis. Graphical Abstract: uf0001